Disaster readiness' influence on the impact of supply chain resilience and robustness on firms' financial performance: a COVID-19 empirical investigation. Issue 8 (18th April 2023) - Ruel, Salomée; El Baz, Jamal
Abstract : This study investigates the impact of supply chain (SC) disaster readiness on SC resilience and robustness and the subsequent impact on firms' financial performance in the context of the COVID-19 outbreak. Drawing on the dynamic capabilities view and organisational readiness for change theory, we provide a theoretical model and assess data gathered of 398 French firms using structural equation modelling. The findings corroborate the role of SC disaster readiness in setting the stage for resilience and robustness. In addition, the results indicate the positive influence of SC resilience on financial performance; however, the effects of SC robustness on performance are not demonstrated. Based on these results, we offer theoretical and practical implications for the extant literature and provide further avenues for research.